Os Projetos regionais de Brasil e Venezuela para América do Sul nos anos Lula da Silva (2003-2010) - Pedroso, Carolina Silva [UNESP] (2014)
Brazilian foreign policy to South America during the years Lula da Silva (2003-2010) was considered emphatic, assertive, aiming to develop its regional environment as part of a larger process of national development. However, analysis of the South American landscape of this period reveals the emergence of an alternative project to Brazil: the Bolivarian. Venezuelan President Hugo Chavez sought to use the oil revenues that flooded their country during the economic boom of the 2000s, to finance based on the ideas of Bolivar and the so-called socialism of the XXI century initiatives. Given the rise of a new regional project, this study seeks to outline how Lula's Brazil managed to ensure the supremacy of his scheme for the region, represented by the Union of South American Nations (UNASUR), compared to alternative presented by Chavez the Bolivarian Alliance for the Americas (ALBA)